A multi-session interpretation modification program: Changes in interpretation and social anxiety symptoms - Beard, Courtney; Amir, Nader (Behaviour research and therapy, 2008)
Previous research suggests that socially anxious individuals interpret ambiguous social information in a more threatening manner compared to non-anxious individuals. Recently, studies have experimentally modified interpretation and shown that this subsequently affected anxiety in non-anxious individuals. If similar procedures can modify interpretation biases in socially anxious individuals, they may lead to a reduction in social anxiety symptoms. In the current study, we examined the effect of a computerized Interpretation Modification Program (IMP) on interpretation bias and social anxiety symptoms. Twenty-seven socially anxious individuals were randomly assigned to the IMP or a control condition. Participants completed eight computer sessions over four weeks. The IMP modified interpretation by providing positive feedback when participants made benign interpretations and negative feedback in response to threat interpretations. The IMP successfully decreased threat interpretations, increased benign interpretations, and decreased social anxiety symptoms compared to the control condition. Moreover, changes in benign interpretation mediated IMP's effect on social anxiety. This initial trial suggests that interpretation modification may have clinical utility when applied as a multi-session intervention.